Guinea-Bissau : Staff Report for the 2013 Article IV Consultation; Debt Sustainability Analysis; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2013)
The staff report for the 2013 Article IV Consultation on Guinea-Bissau highlights the economic development and policies. Guinea-Bissau's medium-term challenges are to diversify its economy, reduce widespread poverty, and generate employment opportunities. Recurrent internal conflicts have negatively affected economic growth, poverty reduction, and social advancement in Guinea-Bissau. The economic performance will depend critically on establishing a visibly inclusive political process while moving toward demobilization, and professionalization of the military forces. In the baseline, uncertainties about implementation of those conditions suggest scope for only a slow and weak recovery, leaving real per capita incomes below 2011 levels until at least 2016.